Patient Specific Induced Pluripotent Stem Cell-Derived Cardiomyocytes for Drug Development and Screening In Catecholaminergic Polymorphic Ventricular Tachycardia - Jehuda, Ronen Ben (J Atr Fibrillation, 2016)
Catecholaminergic polymorphic ventricular tachycardia (CPVT), an inherited arrhythmia often leading to sudden cardiac death in children and young adults, is characterized by polymorphic/bidirectional ventricular tachycardia induced by adrenergic stimulation associated with emotionally stress or physical exercise. There are two forms of CPVT: 1. CPVT1 is caused by mutations in the RYR2 gene, encoding for ryanodine receptor type 2. CPVT1 is the most common form of CPVT in the population, and is inherited by a dominant mechanism. 2. CPVT2 is caused by mutations in the CASQ2 gene, encoding for cardiac calsequestrin 2 and is inherited by recessive mechanism. Patient-specific induced Pluripotent Stem Cells (iPSC) have the ability to differentiate into cardiomyocytes carrying the patient's genome including CPVT-linked mutations and expressing the disease phenotype in vitro at the cellular level. The potency for in vitro modeling using iPSC-derived cardiomyocytes (iPSC-CMs) has been exploited to investigate a variety of inherited diseases including cardiac arrhythmias such as CPVT. In this review we attempted to cover the majority of CPVT patient specific iPSC research studies previously published. CPVT patient-specific iPSC model enables the in vitro investigation of the molecular and cellular disease-mechanisms by the means of electrophysiologycal and Ca(+2) imaging methodologies. Furthermore, this in vitro model allows the screening of various antiarrhythmic drugs, specifically for each patient, also known as "personalized medicine".